‘Hier woont men in de wereld’: Luxe hoogbouw in Nederland tijdens de wederopbouw (Bulletin KNOB, 2021)
In Dutch history the years between 1945 and 1965 are regarded as the period of post-war recovery and reconstruction (wederopbouw). One of the main issues of this period was the urgent need to house the rapidly rising Dutch population. High-rise dwellings were seen as one of the answers and, according to many, desirable. However, after the war, and even into the early 1960s, the construction of high-rise apartment towers was considered suitable for only a small, relatively well-to-do, part of the Dutch population. It was thought that most people would not be interested in living in tall buildings unless there was an element of luxury in both the buildings and the apartments themselves. Most architects and city planners labelled high-rise as unfit for the working class and for families with children. Consequently, most high-rise construction in the 1950s and early 1960s was aimed at a small group of ‘modern’ people, well-educated and perhaps slightly bohemian. Seven of these buildings are studied in this article. They vary in size, height and architectural appearance, but still form a distinct architectural type. As the article points out, these buildings were, and are to this day, very successful. Their success is analysed through a close reading of the buildings themselves and of their location in the urban context. The success of the luxury apartment building is attributed to the following conditions. The buildings were built for a small group of independently-minded people, keen to live a modern and comfortable life. They were even prepared to pay far more for their apartment than most terraced houses would have cost. Secondly, the developers invested in a wide variety of luxury features such as central heating, elevators, roof terraces, a housekeeper, ‘American’ kitchens, lock-up garages and the like. Thirdly, renowned architects were hired to design these luxury buildings. Since it did not concern social housing, the building budgets were rather generous. The architects could therefore design rather stylish buildings with well thought-out floor plans and airy and spacious rooms. Costly and decorative materials were used lavishly. As these buildings were unique, architects could meet the requirements of the building plot as well as of the intended inhabitants. Furthermore, the buildings were invariably built on highly desirable sites. They either overlook a city park, a large pond or a canal, or are in an already established residential area, but always within easy reach of urban amenities.Unlike a considerable part of the social high-rise buildings in Dutch cities built from the early 1960s onwards, many of the luxury apartment buildings are still considered highly desirable places to live, even sixty years after their construction.